The Political Economy of Fiscal Resilience: Evidence from Best Practices in Local Government Liquidity Management - Danang Indrajaya; Anak Agung Ngurah Agung Chandra Nanda Kusuma Kusuma; Muhammad Fikri Al-Banna; Windari Driyastutik (Husnayain Business Review, 2026)
Purpose – This study interrogates a critical yet underexplored phenomenon in subnational finance: the accumulation of local government funds in commercial banks. Moving beyond conventional interpretations of such balances as mere fiscal imbalances, we rigorously examine whether these reserves reflect deliberate liquidity management strategies or systemic governance failures. Methodology/approach – Through a systematic literature review synthesizing global references, we analyze the tension between transparency imperatives in public financial management and the realities of local political pressures. Employing a comparative analytical framework, we integrate insights from fiscal resilience theory, cost stickiness behavior, and digital transformation in the public sector. Findings – Our findings reveal that fund accumulation often constitutes a rational response to rigid expenditure structures and serves as a strategic fiscal buffer against macroeconomic uncertainty. However, the efficacy of this buffer is critically undermined by information asymmetries arising from political connectedness and creative accounting practices, distortions that compromise managerial decision-making and fiscal accountability. Notably, jurisdictions embracing Environmental, Social, and Governance (ESG) principles alongside Technology-Organization-Environment (TOE) frameworks demonstrate significantly higher budget absorption efficiency and public value creation. Novelty/value – This research contributes a nuanced political economy perspective to fiscal resilience literature, offering policymakers evidence-based pathways to transform idle balances into instruments of sustainable local development, without succumbing to political capture or fiscal opacity.